Plant Community Structure and Biodiversity Patterns In Chattogram Metropolitan City of Bangladesh (Bangladesh Journal of Plant Taxonomy, 2022)
The present study aims at investigating the vegetation in different sites of Chattogram metropolitan area following appropriate techniques. In order to enumerate the distribution of species, several diversity indices including Shannon-Winer Index, Pielou’s Evenness and Simpson’s Index were employed. A total of 645 species belonging to 414 genera under 120 families were documented from the studied area for the first time. Of these, 37 species (5.73%) are pteridophytes, 607 species (94.11%) are angiosperms and single representation of gymnosperm (0.16%). Among the recorded species, 384 are medicinal species belonging to 277 genera under 93 families. Bacopa monnieri is a dominant species in the forest area with some co-dominant species like Eichhornia crassipes, Centella asiatica, etc. Moreover, this study provides potential sources to the environmental planners, herbalists, ecologists, taxonomists, ethnobotanists, pharmacists, phytochemists and local administration that would help to plan for future green infrastructure and maintain ecosystem function providing long-term benefits for the city dwellers.Bangladesh J. Plant Taxon. 29(2): 313-344, 2022 (December)